Desempenho produtivos de porcas: 1. efeito do tipo de alojamento na maternidade: 2. efeito da suplementação de aminoácidos na gestação - Osava, Carolina Fonseca (2011)
The present work aimed to evaluate two types of housing sows in late pregnancy in an individual cage and pen, for birth and during lactation, and placental efficiency, correlating it to the performance of post-natal piglets. And also the effect of supplementation of arginine and glutamine after 40 days of gestation of primiparous sows, we analyzed the productive performance and the evolution of litter until weaning. Was followed by 10 primiparous females that with 105 days of gestation, five were housed in conventional cages in the maternity ward and the other five in cages with environmental enrichment of hay. The births were followed, each individually collected placenta and their respective piglets, being weighed and measured the length and color, and accompanied the piglets until weaning. Another 80 primiparous females were subjected to a randomized block design and a factorial: supplementation with 1% arginine, 1% glutamine, 1% AminoGut ® and 05,% +0.5% of the Arginine AminoGut ®, and two gestational periods, from 40 to 85 days of gestation and 40 days of gestation until delivery. Was accompanied by the Parthians, and all production parameters. The type of accommodation during the birth and throughout lactation did not influence the postnatal performance of piglets, but there were positive correlations between placental efficiency and piglet weight at birth, the size of the piglet and the size, weight and color of the placenta. Supplementation of amino acids, arginine, glutamine and AminoGut ® did not influence the total number of births, live births, birth weight, stillbirth, weaning weight. But there was a beneficial effect on the number of mummified and placental efficiency was better in 40 days of supplementation of gestation until delivery in the use of 1% AminoGut ® and the combination of 0.5% Arginine and 0.5% AminoGut®. It was concluded that the managements adopted during pregnancy, be it nutritional or environmental, contribute to a better performance and piglet survival.